Detection of somatic TP53 mutations and 17p deletions in patients with chronic lymphocytic leukemia: a review of the current methods - Maria de Lourdes L.F. Chauffaille; Ilana Zalcberg; Wolney Gois Barreto; Israel Bendit (Hematology, Transfusion and Cell Therapy, 2020)
Chronic lymphocytic leukemia is the most common hematologic malignancy among adults in Western countries. Several studies show that somatic mutations in the TP53 gene are present in up to 50% of patients with relapsed or refractory chronic lymphocytic leukemia. This study aims to review and compare the methods used to detect somatic TP53 mutations and/or 17p deletions and analyze their importance in the chronic lymphocytic leukemia diagnosis and follow-up. In chronic lymphocytic leukemia patients with refractory or recurrent disease, the probability of clonal expansion of cells with the TP53 mutation and/or 17p deletion is very high. The studies assessed showed several methodologies able to detect these changes. For the 17p deletion, the chromosome G-banding (karyotype) and interphase fluorescence in situ hybridization are the most sensitive. For somatic mutations involving the TP53 gene, moderate or high-coverage read next-generation sequencing and Sanger sequencing are the most recommended ones. The TP53 gene mutations represent a strong adverse prognostic factor for patient survival and treatment resistance in chronic lymphocytic leukemia. Patients carrying low-proportion TP53 mutation (less than 20–25% of all alleles) remain a challenge to these tests. Thus, for any of the methods employed, it is essential that the laboratory conduct its analytical validation, documenting its accuracy, precision and sensitivity/limit of detection.